2021
DOI: 10.3920/jiff2020.0057
|View full text |Cite
|
Sign up to set email alerts
|

Information and taste interventions for improving consumer acceptance of edible insects: a pilot study

Abstract: Insects are a sustainable protein source with poor consumer acceptance in developed countries. An Eating Insects Conference and Tasting Demonstration was hosted with a goal of promoting consumption of edible insects. The event consisted of an educational session that provided information about entomophagy followed by a cooking and tasting demonstration of edible insects. Pre- and post-intervention surveys were conducted to assess the effect of the event on participants’ acceptance of entomophagy. Forty-three a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 29 publications
1
25
1
Order By: Relevance
“…Previous reviews have indicated that the concept of eating insects would likely be more appealing to younger people than older people ( 4 , 21 , 22 ). In contrast, the majority of studies (61.1%) in our review concluded that there was no link between age and Westerners' acceptance of edible insects ( 39 , 41 , 42 , 48 , 51 , 55 , 56 , 58 , 61 , 62 , 64 , 66 , 72 74 , 86 , 104 106 , 108 , 109 , 117 ). However, 36.1% of all studies that evaluated the effect of age on consumers' acceptance observed a negative effect of age ( 2 , 64 , 65 , 67 , 71 , 76 , 77 , 87 , 92 , 93 , 97 , 99 , 115 ), which means that younger people had a higher acceptance of insect-based foods than older people, while two studies (5.6%) identified a positive connection ( 49 , 107 ).…”
Section: Resultscontrasting
confidence: 63%
See 3 more Smart Citations
“…Previous reviews have indicated that the concept of eating insects would likely be more appealing to younger people than older people ( 4 , 21 , 22 ). In contrast, the majority of studies (61.1%) in our review concluded that there was no link between age and Westerners' acceptance of edible insects ( 39 , 41 , 42 , 48 , 51 , 55 , 56 , 58 , 61 , 62 , 64 , 66 , 72 74 , 86 , 104 106 , 108 , 109 , 117 ). However, 36.1% of all studies that evaluated the effect of age on consumers' acceptance observed a negative effect of age ( 2 , 64 , 65 , 67 , 71 , 76 , 77 , 87 , 92 , 93 , 97 , 99 , 115 ), which means that younger people had a higher acceptance of insect-based foods than older people, while two studies (5.6%) identified a positive connection ( 49 , 107 ).…”
Section: Resultscontrasting
confidence: 63%
“…Ethnicity does not seem to influence acceptance toward insect-derived foods ( 106 ). Woolf et al ( 106 ) differentiated between six groups to elicit ethnicity: Caucasians, Latino Americans, Pacific Islanders, African Americans, Indian Americans, and participants with “ two or more ethnicities.”…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These concerns arise mainly because of the limited availability of information about the process used to guarantee the innocuity and quality of the insect-derived ingredient [48,66] and its regulations [67] when incorporated into foods. However, this could be substantially improved if potential consumers are educated about the safety and regulations governing edible insect process throughout the added-value chain starting in farms until presented in a meal [68] and by repeated exposure to tasting events involving edible insects without any health-related adverse outcome [69]. [44].…”
Section: Emotional Profiles Of Males Vs Females Before Tastingmentioning
confidence: 99%